2011
DOI: 10.1108/07363761111165930
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health benefits and food purchasing decisions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…More practical considerations stipulate that natural is expressed through the color green, which evokes nature and provokes an emotional reaction, or through the ingredients; natural ingredients help reassure the consumer (Evans et al, 2010). Finally, the information given about the product seems to be important and must be clear and unambiguous (Silayoi & Speece, 2007), mentioning health benefits (Darian & Tucci, 2011) or ecological benefits, in order to reassure consumers in their decision.…”
Section: The Influence Of Emotional and Functional Elements Of Packagingmentioning
confidence: 96%
“…More practical considerations stipulate that natural is expressed through the color green, which evokes nature and provokes an emotional reaction, or through the ingredients; natural ingredients help reassure the consumer (Evans et al, 2010). Finally, the information given about the product seems to be important and must be clear and unambiguous (Silayoi & Speece, 2007), mentioning health benefits (Darian & Tucci, 2011) or ecological benefits, in order to reassure consumers in their decision.…”
Section: The Influence Of Emotional and Functional Elements Of Packagingmentioning
confidence: 96%
“…Additionally, Maruyama and Trung (2007) demonstrate that the underlying reasons for buying fresh food in Vietnamese supermarkets include factors such as brand names, ranges of size and volume, the freshness and the origin of goods. Recently, scholars typically identify food label and package as important determinants of consumer purchasing decision (Akbay & Jones, 2005;Andreas, Panagiotis, & Rodolfo, 2007;Jabir, Sanjeev, & Janakiraman, 2010;Jean & Louis, 2011;Kempen, Bosman, Bouwer, Klein, & van der Merwe, 2011). Hence the following hypothesis has been developed: H1: Product factor has a positive influence on consumer buying behavior.…”
Section: Productmentioning
confidence: 99%
“…The authors found that presence of any illness they examined (cancer, heart disease, diabetes and obesity) in the respondent's family increased the likelihood of buying foods directly from producers; however, it was not possible to identify which of the specific diseases were driving the purchasing decision as they were aggregated into a single variable. Darian and Tucci (2011) found that high nutritional value and the potential to reduce the risk of cancer or heart disease play a vital role in consumers' purchase intentions. Similarly, Nayga, Lipinski, and Savur (1998) found that consumers, particularly those on special diets, placed importance on nutrition and on following dietary guidelines while shopping.…”
Section: Introductionmentioning
confidence: 99%